PENGARUH PERBANDINGAN JAMUR TIRAM PUTIH (Pleurotus ostreatus Jacq) DAN TEPUNG TAPIOKA TERHADAP KARATERISTIK FISIKA, KIMIA PADA ORGANOLEPTIK PEMPEK JAMUR TIRAM - Surono, Surono; Suyatno, Suyatno; Mukhtarudin, Mukhtarudin (Universitas Muhammadiyah Palembang, 2016)
Studying the Effect Comparison White Oyster Mushroom (Pleurotus ostreatus Jacq) and Tapioca Flour Characteristics Of Physics, Chemistry At Pempek Organoleptik Oyster Mushrooms. This study aims to determine the effect of white oyster mushroom comparison (pleorotus ostreatus Jaq) and flour tapoika against kerateristik physics, chemistry on Organoleptik pempek oyster mushrooms. This study was conducted at the Laboratory Alhamdulillah Faculty of Agriculture, University of Muhammadiyah Palembang and Industrial Research and Standards Palembang in December 2014 until the month of August 2015. This study uses Kelompaok Random Design (RAK) are arranged in a non factorial with treatment factor comparisons white oyster mushrooms with flour tapoika which consists of five treatment factors and repeated emapat times. The parameters were observed in this study, for chemical analysis mliputi levels of protein and moisture content that has not pempek fried oyster mushrooms. As for organoleptic tests include color, taste and flavor with hedonic test and rank test pempek texture with oyster mushrooms. The results showed that the influence of white oyster mushroom comparison (Pleorotus ostreatus Jaq) and tapioca flour very significant effect on the moisture content and protein pempek white oyster mushroom. Protein content and high water content contained in the treatment J5 (white oyster mushrooms 1.5 parts: 0.5 parts tapioca flour) with an average value of 10.61%, and 64.97%, while the protein content and low water content contained in the J1 treatment (white oyster mushrooms 0.5 parts: 1.5 parts tapioca starch) with an average value of 5.34% and 51.33%. Organoleptic results using hedonic test on pempek white oyster mushroom (Pleorotus ostreatus Jaq) for color, flavor and aroma. For color does not affect nayata with the highest score at the J1 treatment with an average value of 3.64 (rather preferred criteria), while the taste and aroma of real effect. Highest sense J3 treatment with an average value of 3.60 (criteria rather preferred) and the highest taste J1 treatment with an average value of 3.64 (criteria rather preferred). Significant level of resilience. J3 treatment by comparison oyster mushroom and tapioca flour (white oyster mushroom 1, section: tapioca flour 1, section) produce the best level of elasticity with an average value of 2.84 (criteria somewhat chewy).